english English - Ryan Firdaus Yusuf; Felix Goenadhi (Bogor Hospitality Journal, 2024)
The study focuses on Taman Wisata Alam Gunung Papandayan, a natural tourist destination situated in Garut Regency, West Java. Its objective is to assess and pinpoint areas for improvement within the framework of the 3A's concept, encompassing Attraction, Accessibility, and Amenities. Employing a descriptive qualitative research methodology, the research population consisted of both visitors and an employee from Taman Wisata Alam Gunung Papandayan, totaling 4 visitors and 1 employee. Data collection involved observations, interviews, and documentation, addressing specific research questions. The study utilized Importance-Performance Analysis to derive its findings. The results indicate three key areas requiring enhancement: nature conservation, provision of trash cans, and places of worship. Notably, the findings highlight deficiencies in natural preservation efforts, insufficient trash cans with a lack of organic and non-organic waste bins, and a limited number of places of worship. The originality and value of this study lie in its identification of crucial factors for improvement within Mount Papandayan Nature Park, guided by the comprehensive 3A's framework (attractions, accessibility, and amenities).